Robotic formation: initialisation, trajectory planning and decentralised control. (25th September 2008) - Nguyen, A.D.; Ngo, V.T.; Ha, Q.P.; Dissanayake, G.
Coordination of a group of mobile robots in desired formations requires an integration of motion planning and control strategies subject to communication bandwidth limitations. An architecture combining virtual structure and leader following techniques is proposed in this paper. The robots are initialised using a new Virtual Robot (VR) tracking and l-l control framework to establish an arbitrary formation without singularities involved and inter-robot collision. Path planning is performed using the modified A* search, coupled with a proposed smoothing technique to generate feasible trajectories with mobile robots, dynamic and kinematic constraints taken into account. Safe trajectories are obtained based on the predefined formation configuration and the given workspace, where obstacles are avoided by adjusting robot trajectories or by changing formation of the robots appropriately. To accommodate the restriction in information exchange, a decentralised approach is proposed to implement the global feedback controller for the formation by using linear functional observers. The proposed architecture is tested through simulation and experiments to verify its validity.